STRATEGI PENGELOLAAN WARISAN BUDAYA BERBASIS PERAN MASYARAKAT DI KECAMATAN LASEM KABUPATEN REMBANG - Riris Purbasari (Universitas Islam Sultan Agung Semarang, 2018)
ABSTRACTLasem is one of Sub Districts in Rembang Regency located in north coast of central part of Java Island. The strategic position of Lasem that is located on maritime and over-land trading route has made this area since 500 BC inhabited and has passed many different periods of human settlement ranging from prehistory, classic (Hinduism-Buddhism), Islam, colonial periods and until today. That long period of human settlements has left for us now heritages of various cultural influences including Javanese, Chinese, European, Hinduism-Buddhism, and Islamic culture. Heritage is finite and un-renewable in its nature so that it needs to be managed in order to outlive and to be inherited to the next generations. In Lasem, people have been relatively aware of that. Communities in Lasem represented by their organizations have their agendas of appreciating and preserving their heritage. However, they did them individually or not in good coordination of each other. The situation then generates an idea of coordinating activities done by communities in Lasem. Active role of those communities have to be guided and developed so that the purpose of appreciating and preserving their heritage can be achieved. This is intended as for management of heritage can be done continually. Key words: Lasem, Heritage, Heritage Management, Community based ABSTRAKLasem adalah sebuah kecamatan di Kabupaten Rembang yang terletak di pesisir utara Pulau Jawa bagian tengah. Lasem memiliki potensi luar biasa antara lain terletak di jalur perdagangan laut dan darat yang telah didiami sejak 500 tahun Sebelum Masehi diawali oleh manusia masa prasejarah, klasik, Islam, kolonial, hingga saat ini. Masa hunian manusia yang panjang di Lasem meninggalkan warisan budaya dengan berbagai pengaruh budaya diantaranya Jawa, Cina, Eropa, Klasik, dan Islam yang sebagian masih dapat dijumpai hingga saat ini. Namun demikian, warisan budaya bersifat terbatas dan tidak dapat diperbaharui sehingga perlu untuk dikelola agar berusia lebih panjang agar dapat diwariskan kembali kepada generasi selanjutnya. Pengelolaan warisan budaya yang dilakukan oleh masyarakat Lasem selama ini masih bersifat terpisah-pisah satu sama lain. Namun, peran aktif masyarakat terus dibina dan ditingkatkan agar tujuan pengelolaan warisan budaya yang berbasis masyarakat dapat segera dicapai. Pemilihan pengelolaan oleh masyarakat setempat bertujuan agar pengelolaan yang dilakukan dapat berkelanjutan. Kata Kunci: Lasem, Pengelolaan, Warisan Budaya, Basis Masyarakat.